A Cognitive-Semantic Approach To The Interpretation Of Death Metaphor Themes In The Quran - Khan, Sardaraz; Roslan, Ali (Universiti Sultan Zainal Abidin, 2019)
In previous literature, conceptual metaphor has been used as a comprehensive cognitive tool to explore systematic categorization of concepts in the Quran. Death metaphor themes have either been studied from rhetorical or conceptual perspectives, but metaphor interpretation needs both linguistic and conceptual knowledge. This paper will explore the function of both linguistic and conceptual knowledge in metaphor interpretation in the Quran. This paper has used the technique of key words and phrases for data collection and metaphor identification procedure (MIP) for metaphors identification. Thirteen conceptual metaphors were found in the data. The key conceptual metaphors were analyzed through the lexical concept cognitive model theory (hereafter LCCM) to find out the functions of linguistic and conceptual knowledge in metaphor interpretation. The findings reveal that conceptual metaphor gives only relational structure to the linguistic metaphoric expressions, whereas interpretation needs integration of both linguistic and conceptual knowledge. Conceptual simulation of metaphoric expressions is a multilinear process of multiple conceptual schemas and language. The findings also reveal that LCCM needs the tool of intertextuality for clash resolution of contexts in text interpretation. This paper holds that meaning construction depends upon multilinear processing of conceptual schemas and language. Furthermore, it asserts that the gap in LCCM may be resolved through the tool of intertextuality in metaphor comprehension. This study suggests further studies on relationship between conceptual schemas and lexical behaviour and an elaborate model for text interpretation, combining LCCM and intertextuality.